2010
DOI: 10.1515/jpm.2010.095
|View full text |Cite
|
Sign up to set email alerts
|

Genome profiles in maternal blood during early onset preeclampsia and towards term

Abstract: a possible type 1 immune response was identified both during preeclampsia and towards term. In pre-eclampsia a premature activation of leucocytes might be present.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…Matrix metalloproteinase ( MMP)-9 was found to be differentially expressed in that study, but was not confirmed in our qRT-PCR analysis. Dahlstrom et al, using the PAX gene Blood RNA system, reported 19 differentially expressed genes between 8 early-onset PE and 8 normal pregnant women [195]. Only lower expression of CCR3 (CC-chemokine receptor 3) gene in late-onset PE was confirmed in our study.…”
Section: Discussionsupporting
confidence: 66%
“…Matrix metalloproteinase ( MMP)-9 was found to be differentially expressed in that study, but was not confirmed in our qRT-PCR analysis. Dahlstrom et al, using the PAX gene Blood RNA system, reported 19 differentially expressed genes between 8 early-onset PE and 8 normal pregnant women [195]. Only lower expression of CCR3 (CC-chemokine receptor 3) gene in late-onset PE was confirmed in our study.…”
Section: Discussionsupporting
confidence: 66%
“…Maternal inflammatory reactions may change toward the end of the term. The study evaluating genome signaling in peripheral blood during preeclampsia and toward the end of the term using microarrays revealed upregulation of TNFSF15 (Dahlstrøm et al, 2010).…”
Section: Tnfsf15mentioning
confidence: 99%
“…Previous investigations have also shown the effect of vitamin D levels on peripheral blood gene expression during pregnancy and in preeclampsia (10,11). Global gene expression profiling has the potential to identify representative pathway genes that might point to the underlying molecular mechanism of preeclampsia (12)(13)(14)(15). Therefore, we performed a nested case-control study in the VDAART to identify vitamin D gene signatures related to preeclampsia during early pregnancy.…”
Section: Introductionmentioning
confidence: 99%